THE IMPORTANCE OF LEARNING ENGLISH IN THE MODERN WORLD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the importance of the English language in the modern world. It analyzes the role of English in international communication, education, business, culture, and personal development. The paper discusses the reasons behind English’s global dominance and highlights both the benefits and challenges of learning it. The study concludes that English is not merely a tool for communication but a key to accessing global opportunities and success in today’s interconnected world.